A simultaneous presentation of drug-induced lupus with drug-induced ANCA vasculitis secondary to hydralazine use in a patient with sarcoidosis. Issue 2 (3rd April 2019) - Espinosa, Maria Catalina; Ding, Belicia; Choi, Kati; Cohen, Daniel N.; Marcelli, Marco; Ifoeze, Onome Whiteru
Abstract: Frequently used in the management of hypertension and heart failure, hydralazine is associated with the development of adverse rheumatologic side effects. The authors highlight a unique case of drug-induced lupus and drug-induced anti-neutrophil cytoplasmic antibody (ANCA) vasculitis from hydralazine use in a 50-year-old man with sarcoidosis and hypertension.